Respuesta :

Answer:

Fourth term: [tex]a_4 = 9 * (\frac{\sqrt{3}}{3})^{(4 - 1)}[/tex] = [tex]9 * (\frac{\sqrt{3}}{3})^{3}[/tex] = [tex]\sqrt{3}[/tex]

Fifth term: [tex]a_5 = 9 * (\frac{\sqrt{3}}{3})^{(5 - 1)}[/tex] = [tex]9 * (\frac{\sqrt{3}}{3})^{4}[/tex] = 1

Sixth term: [tex]a_6 = 9 * (\frac{\sqrt{3}}{3})^{(6 - 1)} = 9 * (\frac{\sqrt{3}}{3})^{5} =\frac{\sqrt{3}}{3}[/tex]

Step-by-step explanation:

The geometric progression is:

[tex]9, 3 \sqrt{3}, 3...[/tex]

The first term, a, is 9

To find the common ratio, r, all we have to do is divide a term by its preceding term.

Let us divide the second term by the first:

[tex]r = \frac{3\sqrt{3}}{9}\\ \\r = \frac{\sqrt{3}}{3}[/tex]

That is the common ratio.

Geometric progression is given generally as:

[tex]a_n = ar^{(n - 1)}[/tex]

where a = first term

r = common ratio

[tex]a_n[/tex] = nth term

We need to find the 4th, 5th and 6th terms.

Fourth term: [tex]a_4 = 9 * (\frac{\sqrt{3}}{3})^{(4 - 1)}[/tex] = [tex]9 * (\frac{\sqrt{3}}{3})^{3}[/tex] = [tex]\sqrt{3}[/tex]

Fifth term: [tex]a_5 = 9 * (\frac{\sqrt{3}}{3})^{(5 - 1)}[/tex] = [tex]9 * (\frac{\sqrt{3}}{3})^{4}[/tex] = 1

Sixth term: [tex]a_6 = 9 * (\frac{\sqrt{3}}{3})^{(6 - 1)} = 9 * (\frac{\sqrt{3}}{3})^{5} =\frac{\sqrt{3}}{3}[/tex]